Job application resumes : the effects of professional photographs and leadership experience on recruiter decisions. - Hong, Weiming. (2008)
The present study explored the effects of professional photographs and leadership experience on the evaluation of female job applicants in the initial screening phase of the selection process. One hundred and fifty-five recruiters screened r?sum?s of fictitious fresh graduates for real job vacancies. The recruiters were given r?sum?s that differed in the leadership experience in co-curricular activities. A passport-sized head-and-shoulders photograph of a female with or without a professional image was attached to the first page of each r?sum?. A control condition with no attached photograph was also included. Recruiters judged how likely they would offer an interview to the applicants. Results indicated that r?sum?s with photographs of applicants with professional image were given higher ratings of being offered an interview than r?sum?s with photographs of applicants with non-professional image and no photographs attached. Applicants with high leadership were also rated higher in terms of the likelihood of being offered an interview. Implications for the field of human resource management and suggestions for future research are offered.